Studi Penggunaan Asam Traneksamat pada Penderita Tuberkulosis dengan Hemoptisis di Instalasi Rawat Jalan Rumah Sakit Umum Haji Surabaya - Yuni, Santi Eka; Hasmono, Didik; Kasih, Elisabeth; Ayumuyas, Nur Palestin (Jurnal Farmasi Sains dan Terapan, 2018)
Tuberculosis is one of the world's health problems, especially in developing countries with coughing in the form of blood (hemoptysis) as a sign of this disease. Tranexamic acid can be used as one of the treatments for hemoptysis. Tranexamic acid is a synthesis derivative of aminolenic acid which provides antifibrinolytic effects through reversible blocking of lysine binding sites on plasminogen molecules and inhibits plasmin. This study aims to analyze the pattern of use of tranexamic acid in tuberculosis patients with hemoptysis including dosage, frequency and duration of use in the Outpatient Installation of Surabaya Haji General Hospital. The study was conducted observationally with a retrospective method on medical records of patients diagnosed with tuberculosis with hemoptysis and received treatment for tranexamic acid, then analyzed descriptively. Sampling was done by purposive sampling, from January 1, 2016 to December 31, 2017. From the results of the study, the use of tranexamic acid single dose (3x500mg) as many as 2 patients (67%), 500 mg intravenously as many as 1 patient (33%) and combination with Vitamin K as many as 3 patients. The highest duration of use was 3 days in 11 patients (56%). The use of tranexamic acid in hemoptysis patients related to dose, frequency and duration of use is in accordance with the existing literature.